AN ANALYSIS OF HOUSEHOLD CONSUMPTION EXPENDITURES IN EA-18 - Tapsin, Gulcin; Hepsag, Aycan (European Scientific Journal, ESJ, 2014)
Constituting about two thirds of the gross domestic product, household consumption expenditures are a significant financial planning tool. Household consumption expenditures are also considered a primary indicator of economic-wellbeing. Therefore, it has an important place both in macroeconomic theory and empirical studies carried out in this field. The consumption function often referred to as the relationship between income and consumption has taken place in economic literature since Keynesian General Theory. Consumption theories analyzed by Keynes’ Absolute Income Hypothesis, Friedman’s Permanent Income Hypothesis, Modigliani, Ando and Brumberg’s Life Cycle Income Hypothesis and Dusenberry’s Relative Income Hypothesis. This study aims to analyze the household consumption expenditure in EA-18. Panel Data model in this study covers the data between the years of 2000-2012. Gross domestic product (GDP) is used as a proxy for income. The data in terms of dollar are constant according to the base year of 2005 and have been taken from World Development Indicators Data Base.